Analisis Harga, Manfaat, Dan Norma Subyektif Terhadap Minat Menggunakan E-Wallet - Fitria, Lailani; Eliza, Rispa; Syafwandi, Syafwandi; Z, Zulkifli (Innovative: Journal Of Social Science Research, 2024)
Abstract Research was conducted to find out about prices, benefits and subjective norms regarding interest in using e-wallets. The data analysis method is descriptive qualitative, namely finding out topics, news and articles related to the variables above using references from Google Scholar and Mendeley. The research results show that the price variable has an influence on 470 respondents who are dominated by the city of Pekanbaru. Furthermore, the perception of benefits was 346 respondents located each in Denpasar as many as 90 people and North Sumatra as many as 256 people. And the subjective norms were 837 consisting of 210 respondents using TAM, 427 respondents using TAM UTAU while 200 respondents in Bandung used TAM UTAUT2. This shows that a total of 1,653 respondents from various circles and using different methods can provide information that is needed for similar research.